A CASE STUDY ON POSTERIOR REVERSIBLE ENCEPHALOPATHY SYNDROME WITH ECLAMPSIA - PORANKI, VATHSALYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Posterior reversible neurological disorder syndrome may be a clinical syndrome characterized by varied conditions conferred by the patient need medicine, tomography diagnosing to advocate the treatment. Gestational toxemia of pregnancy toxemia begins throughout the pregnancy because the underlying medical condition of the mother later causes toxemia. These two clinical situations were approached by observatory medical aid depending on the mother’s health and nutrition. Here, this case study is of a 37-year-old who conferred in post-pregnancy cesarean with seizures, high pressure, disturbed mental state, and high blood glucose levels. Pregnancy-related clinical syndromes are hugely dependent on the mother’s well-being. Syndromes during pregnancy not solely influence the mother’s health additionally cause severe hurt to the fetus because leading to rise in premature births, fetal death rate, and inflicting psychological distress to the mother’s mental health.